The Chinese Graduate Unemployment Crisis 2023. A Comprehensive Geo-Educational Study. - Miller, Antony D.; Batsaikhan, Enkhbayar; Gankhuyag, Zolzaya; Ganbaatar, Jargalmaa (International Journal of Scientific Research and Management (IJSRM), 2023)
It is said that “Graduation marks the end of one era and the beginning of a new one.” Lemire, S. (2023). As for Graduates of the People’s Republic of China, the new means a future employment struggle. As this is one of the most discussed topics in Asia, this comprehensive research study investigates the trials and tribulations involved in the pursuit of work for graduating students in one of the most competitive job markets in the world. Unearthed within this body of work, the team of researchers discovered that a bachelor’s degree is not sufficient even to obtain a first position. Many company recruiters in 2023 now seek postgraduate students instead, due to the intense competition of the recently graduated pool of alumni to apply for first-tier office-oriented positions. In addition to this burdensome or arduous outlook, to find gainful employment. i.e., These graduates have requested higher salaries in the major cities to be proportional to the rising standard of living costs, as recruiters usually offer a standardized lower wage for newcomers at job fairs. Therefore, the psychological effects and ramifications for the new generation in China, have both been delineated and discussed in this paper.